Redox thiol status plays a central role in the mobilization and metabolism of nitric oxide in human red blood cells - Lopes de Almeida, José Pedro (2020)
Copyright © 2008 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.